(3GdJNWjW GdfGLM dGNJjGQ GdegfI GdefGSHIs - (3gGQT, hfOjs; (3LGcShf, TGQds ((3HjQhJs (3GdOGQ GdYQHjI ddYdhes, 1998)
(3GdYed LRA ege aj MjGI GdEfSGf jYJeO Ydjg ddMUhd Ydi GdeONhd GdPj jQZH GdcKjQ efG HRjGOJg(B. (3hgPG eecf ef NdGd GSJNOGe GdegGQGJ GdTNUjI HeG jJdGAe eY GdGdJRGeGJ hGdGgJeGeGJ GdebGHdI(B. (3dcqf GdbqdI efG ef jHPd GdcKjQ ef GdLgO aj GdJNWjW dfhY GdegfI GdJj jQjOgG; dcf GdJacjQ aj GdZGjI GdJj fbUOgG NdGd GdYed gh TjA jLH Ydi GdLejY JWHjbg ef NdGd GdMjGI GdegfjI(B. (3hjecf Pdc ef NdGd GdYed HSdSdI HSjWI ef GdNWhGJ GdJj jTQMgG gPG GdcJGH hGdJj jecfc ef NdGdgG eSGYOI faSc Ydi JhVjM eG JQjOg heG gj NjGQGJc hcja jMUd GdJbOe Edi GdEeGe ef NdGd GdYed GdeOQhS GdJj jJhGab hegGQGJc hJWdYGJc GdeSJbHdjIs
(3gPG GdcJGH JQLeI GdCUd GdGfcdjRj (BSuccessful career plannings
12
Keywords: (3GdJNWjWs; (3GdfLGM GdEOGQjs